Cost-effective Rural Electrification with Capacitor Coupled Substations: A Simulation Approach - Nene, Sinqobile Wiseman; Abe, Bolanle Tolulope; Nnachi, Agha Francis (Current Approaches in Engineering Research and Technology Vol. 5, 2024)
The present study highlights cost-effective Rural Electrification with Capacitor Coupled Substations. Electricity plays a crucial role in the economic development of any developing country. In Sub-Saharan African countries (SSA), there are still numerous rural communities that have limited access to electricity. Access to electricity in rural areas is extremely limited, but it is crucial for all citizens. The population in rural areas of sub-Saharan African countries is generally low, making it economically unfeasible to implement conventional rural electrification (CRE) projects due to the high cost of establishing the necessary distribution infrastructure. The Capacitor Coupled Substation (CCS) technology is one possibility for rural electrification (URE) that can be investigated to alleviate this cost issue. It has been discovered that CCS is an affordable option for providing rural areas with electricity. The research is necessitated by the need to offer cost-effective technology for supplying electricity to sparsely populated communities. This paper examines the impact on the transmission network when a 400kV/400V CCS is connected to it. The system response when a CCS is connected to the network was modelled using MATLAB/Simulink. The results, based on a fixed load of 80kW, showed negligible interference on the transmission line voltage. However, there was minor impact on the parameters downstream of the tapping point. These findings were further supported by introducing a fault condition to the CCS, which showed that interferences with the CCS could affect the overall stability of the transmission network downstream of the tapping node, similar to the behavior of an unstable load. This study only focused on the simulation of a basic system with a fixed load and limited fault scenarios. This, therefore, did not analyze a dynamic response under various conditions. The proposed CCS-CNT will be used for power tapping and power injection on the transmission line through classical control of CNT.